An Analysis of Interference from Javanese in the Pronunciation of ïïï, ïïï and ïï£ï in English by the Students of Faculty of Letters in Gajayana University - Dewi, Pradnya Paramita (Universitas PGRI Yogyakarta, 2014)
AbstrackEnglish Â as one of the international languages has been learned by the students of Faculty ofÂ Letters in Gajayana University. In learning English as foreign language, most learners haveÂ problem Â in Â pronunciation, Â especially Â in Â the Â way Â they Â pronounce Â the Â sound Â of Â the Â targetÂ language. Â Mispronunciations Â which are produce by the learners is caused by the interferenceÂ of the source language or first language. The object Â of this research Â is the students of FacultyÂ of Letters in Gajayana University 2005/2006 intake who are Â native speakers of Javanese Â andÂ have Â been Â done Â phonology Â class. Â Some Â specific Â sounds Â are Â discussed Â in Â these Â researchÂ namely Â English Â sounds Â of Â inter-dental Â fricativeïïï, Â ïïï Â and Â alveolar Â approximantïï£ï. Â TheÂ finding of the research are Â some interferences occur in pronouncing Â those sounds, they are 1)Â voiceless Â inter-dental Â fricative Â ïïï Â is Â pronounced Â using Â voiceless Â dental Â stop Â ïï´ïï, Â aspiratedÂ voiceless dental stop Â ïï´ïïï, voiced dental stop Â ïï¤ïï, and voiceless palato-alveolar affricate Â ïïµïï.Â 2).Voiced Â inter-dental Â fricative Â is Â pronounce Â using Â voiceless Â dental Â stop Â ïï´ïï, Â aspiratedÂ voiceless dental stop Â ïï´ïïï, voiced dental stop Â ïï¤ïï, and voiceless palato-alveolar affricate Â ïïµïï.Â 3).Voiced Â alveolar Â approximant Â ïï£ï Â is Â pronounced Â using Â voiced Â alveolar Â trillïï²ï. Â 4). Â thepossible reasons for the interferences made are based on the similarity of characteristics in theÂ state of vocal cords, place of articulation, and manner of articulations.Keyword: interference